2021
DOI: 10.5937/fme2101128p
|View full text |Cite
|
Sign up to set email alerts
|

Fiber orientation effect on fracture toughness of silk fiber-reinforced zeolite/HDPE composites

Abstract: The aim of this work is to investigate the fracture toughness and deformation of silk fiber (SF)-reinforced zeolite (Z)/high density polyathylene (HDPE) composites. The chopped SFs are arranged in the thickness middle of the dry mixture of Z/HDPE powder that has been prepared in a mold. Composites were produced by the compression molding to produce double-edge notch tensile (DENT). The fracture toughness characterization was carried out based on essential work of fracture method. The results show that the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a number of publications [18][19][20][21][22][23], it was shown that this aim could also be achieved by adding whisker components, which increase the bending strength and fracture toughness of composites. For example, in [19], hBN phases were successfully fabricated via the highpressure sintering of a mixture of SiC w and cBN nanopowders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a number of publications [18][19][20][21][22][23], it was shown that this aim could also be achieved by adding whisker components, which increase the bending strength and fracture toughness of composites. For example, in [19], hBN phases were successfully fabricated via the highpressure sintering of a mixture of SiC w and cBN nanopowders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biopolyols that are synthesized from vegetable oils are a great alternative to replace petrochemical polyols. Oleochemical polyols have several characteristics, such as flexible, mechanical and chemical resistant, hard, and hydrophobic (Borowicz, Paciorek-Sadowska, and Isbrandt, 2020;Purnomo, Setyarini, and Anggono, 2020;Lavrenyuk, Parhomenko, and Mykhalichko, 2019). They are required in the manufacturing industries such as flooring, coatings, and foaming in the polymer industry, polyols are compounds that contain hydroxyl function groups that can be used for other chemical reactions.…”
Section: Introductionmentioning
confidence: 99%